MG-110 Intravenous neonatal gene therapy corrects GM2 gangliosidoses in sandhoff mice for 'long-term', by using an aav expressing a new hexosaminidase variant. (4th December 2015) - Osmon, Karlaina JL; Woodley, Evan; Thompson, Patrick; Ong, Katalina; Karumuthil-Melethil, Subha; Mark, Brian; Mahuran, Don; Gray, Steven J; Walia, Jagdeep S
Abstract : Background: GM2 gangliosidosis is a group of neurodegenerative disorders, characterised by the malfunctioning HexosaminidaseA (HexA) enzyme, for which there is no treatment. HexA is composed of two similar, but non-identical subunits, alpha and beta, which interact to hydrolyze GM2 gangliosides. Mutations in either subunit result in the development of GM2 gangliosidosis. The malfunctioning HexA is unable to cleaving GM2 ganglioside, whose accumulation within the neurons of the central nervous system (CNS) is neurotoxic. The resulting neuronal death induces the primary symptoms of the disease; motor impairment, seizures, and sensory impairments. Objectives: The aim of this study is to observe the long-term in vivo affects of a novel Hex isoenzyme, HexM treatment in a Sandhoff (beta-deficient) mouse model. Design/method: Our methods include intravenous injections of neonatal mice with self-complementary vector expressing HexM at day 0–1. We monitored one cohort for 8 weeks and another cohort long-term for biochemical and behavioural analyses. Results: Through the enzymatic and GM2 ganglioside lipid analyses, we see that with a slight increase in enzyme activity, there is a significant increase in the clearance of GM2 gangliosides. On behavioural tests, the treated mice outperform their knockout age matched controls. While the untreated controls die by 15 weeks, treated animals survived to x̄=41.77 weeks. The molecular analyses reveal a uniform distribution of the vector in the CNS. Conclusions: The neonatal delivery of our newly synthesised viral vector expressing HexM to the Sandhoff mice provided long-term correction of the disease. This study will have implications not only for treatment of Sandhoff, but also Tay-Sachs disease (alpha-deficiency).